Articulating Threats/Threatening Articulations: The Discursive Impact of Persistent Organic Pollutants (POPs) on Local Systems of Meaning - Pötzsch, Holger (2010)
This paper deals with the threats posed by persistent organic pollutants (POPs) to Arctic populations. It does not primarily focus on the negative impacts these substances have on ecosystems and human organisms, but rather directs its attention to the potentially disruptive effects the articulation of these threats might have on Arctic communities and systems of meaning. I employ the theoretical framework developed by Ernesto Laclau and Chantal Mouffe to conceptualise the articulation of threats as different forms of discursive interaction between politico-scientific and local discourses. In providing a close reading of three sets of scientific texts pertaining to POPs in the Arctic, I show that each of these implies a particular form of discursive interaction - overcoding, semiotisation, and interdiscursive translation – which entail widely different effects on local frameworks of meaning. Finally, I apply some of Foucault’s ideas in order to direct attention to the particular form of politics underlying these forms of interaction between discourses.